1988
DOI: 10.1111/j.1440-1681.1988.tb01026.x
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Physical Integrity and Metabolic Viability of the Perfused Human Placental Lobule

Abstract: 1. Peripheral lobules of term placentae obtained from healthy females at Caesarian section were perfused using separate maternal and fetal circulations for 6 h periods under either oxygenated or anoxic conditions. 2. Markers of physical integrity during setting-up and initial perfusion were establishment of dual perfusion within 25 min of placental delivery, pressure in the fetal capillary network less than 40 mmHg, leakage of perfusate from fetal to maternal compartments less than or equal to 2 ml/h, and over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
2

Year Published

1993
1993
2004
2004

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 17 publications
1
12
2
Order By: Relevance
“…Although the ␤-hCG production we observed was within one standard deviation of that reported for viable, oxygenated perfusion (Cannell et al, 1988), the standard deviations in previously published data were much larger than our figures. This is consistent with the findings of Boal et al (1997), who demonstrated that with 4 h of perfusion, AZT caused a significant reduction of ␤-hCG secretion compared with nonexposed placentas.…”
Section: Resultscontrasting
confidence: 55%
See 4 more Smart Citations
“…Although the ␤-hCG production we observed was within one standard deviation of that reported for viable, oxygenated perfusion (Cannell et al, 1988), the standard deviations in previously published data were much larger than our figures. This is consistent with the findings of Boal et al (1997), who demonstrated that with 4 h of perfusion, AZT caused a significant reduction of ␤-hCG secretion compared with nonexposed placentas.…”
Section: Resultscontrasting
confidence: 55%
“…Biochemical and biophysical parameters of the perfusions presented in Table 1 are, in general, consistent with published values (Illsley et al, 1984;Cannell et al, 1988). Although the ␤-hCG production we observed was within one standard deviation of that reported for viable, oxygenated perfusion (Cannell et al, 1988), the standard deviations in previously published data were much larger than our figures.…”
Section: Resultscontrasting
confidence: 53%
See 3 more Smart Citations